Heavy metal removal Arsenic (As) from alkaline water by modified biochar - Hui, Tom; Umbarila, Sabrina; Wang, Bing; Chen, Tongji; Halleri, Rui (Journal of Functional Materials and Applied Engineering, 2024)
Transformation of arsenic in the nature have been a focal point in environmental science research. Particularly in alkaline environments, the mobility and bioavailability of arsenic are relatively high, increasing the complexity of remediation. Biochar, due to its rich pore structure and good stability, is extensively used in the cleaning of heavy metal polluted water bodies. However, its ability to immobilize arsenic is limited by the electrostatic repulsion caused by its surface negative charge. Studies have shown that introducing cations can effectively enhance biochar's ability to immobilize arsenic, with calcium (Ca) being a key research focus due to its high affinity for arsenic. Nevertheless, the interaction mechanisms between biochar and arsenic with existance of calcium under alkaline conditions remain unclear, and the immobilization effects of different forms of calcium-based modified biochar need further investigation. Therefore, this study first explored the interactions between different components of biochar and arsenic in a calcium-rich system. Secondly, novel composite biochar materials were prepared by co-pyrolysis of wheat straw with different calcium-based materials. Adsorption was conducted to investigate their elimination rate for arsenic(V). Combined with material characterization, adsorption kinetics, and isotherm fitting, the key adsorption mechanisms of different biochars under Ca-rich conditions were revealed, aiming to provide a scientific basis for the efficient treatment of alkaline arsenic-contaminated wastewater. To improve the immobilization effect of biochar on arsenic(V), calcium sulfate was co-pyrolyzed with wheat straw at 800°C to prepare modified biochars with different calcium forms, labeled as SBC-800. Maximum adsorption was 861.6 mg per gram. The kinetics of adsorption followed the pseudo second order model and were controlled by intraparticle diffusion. Thermo-dynamic indicated that adsorption process of arsenic(V) by SBC-800, it was spontaneous, endothermic, and also accompanied by an increase. Mechanistic studies revealed that the removal of arsenic(V) by SBC-800 achieved efficient arsenic(V) removal through co-precipitation, complexation, redox reactions, and pore filling